MAGNETIC-FIELD DEPENDENT MICROWAVE-ABSORPTION IN HIGH-TC SUPERCONDUCTING CUPRATES - Janes, R; Liu, R; Edwards, P; Stevens, A; Symons, M (1991)
A strong microwave absorption at low magnetic fields is observed for a variety of metallic cuprates below their critical superconducting transition temperatures (Tc) using conventional electron paramagnetic resonance (EPR) instrumentation. The low-field microwave signal was investigated in the following high-temperature superconductors, YBa2Cu3O 7-x (Tc = 95 K), GdBa2Cu3O 7-x (Tc = 95 K), YBa2Cu4O 8 (Tc = 75 K), (Bi1.6Pb0.4)Sr 2Ca2Cu3Oy (Tc = 115 K), Pb0.5Bi2Sr2Ca2.5Cu 4.5Oy (Tc = 118 K) (Tl0.5Pb 0.5)Sr2(Ca0.8Er0.2)Cu 2Oy (Tc = 115 K), Tl2Ba 2Ca2Cu3Oy (Tc = 118 K), TbTl2Ba2Cu3Oy (Tc = 84 K), Tl2Ba2Ca2Cu3O10 (single-crystal, Tc = 118 K) and Bi2Sr 2CaCu2O8 (single-crystal, Tc = 80 K). We have investigated the usefulness of the technique as a practical non-intrusive method for screening potentially superconducting samples, with particular emphasis on sensitivity, the effect of microwave power and the inherent problems of studying signals at small magnetic fields. In the latter regard, we have also carried out studies using a radiofrequency EPR spectrometer operating at 300 MHz, which facilitated detailed calibration of the 0-200 G region, where the signal is most intense.